Kesan amalan prinsip pengurusan kualiti ISO 9001: 2008 dan kepuasan pelanggan keatas gelagat komunikasi dalam pendidikan tinggi - Mohd. Noor Azizaman, Nur Mazreen (2013)
Quality management principles are critical in identifies the service quality in higher education sector. The research identifies practices that affect students' satisfaction and communication behaviors. Hence this study was conducted to (i) identify the level of Quality Management Principles (student focus, involvement of staff, continuous improvement and factual approach to decision-making) in UTM, (ii) determine the effect of QMP on student satisfaction, (iii) determine the impact of student satisfaction on communication behaviors (WOM) and (iv) investigate the effect of mediating variables-student satisfaction on the relationship between the QMP and communication behavior. By using a stratified sampling technique, 364 questionnaires were distributed and 351 accepted and used for data analysis which has been distributed to final year students from five faculties which is FPPSM, FKA, FKM, FKE and FAB. A result of questionnaires has been analyzed using SPSS (Statistical Package For Social Sciences, Version 20.0 For Desktop). The results showed that all four of the QMP (student focus, involvement of staff, continuous improvement and factual approach to decision-making) in UTM is high (mean values above 3.68). Regression analysis also showed that the practice of QMP is significant and have a positive impact on student satisfaction and positive relationship between student satisfaction and student communication behavior (WOM). Hierarchical regression analysis showed that affect student satisfaction as a mediating between the QMP and the practice of communication behavior